Good Corporate Governance, Profitability, and Sustainability Report Disclosure: The Moderating Role of Firm Size - Nesya Aqillah Santoso; Frido Simatupang (Universitas KH. Abdul Chalim Mojokerto, 2026)
Over time, companies are required to be more than just profit-oriented, but also responsible for people and the planet, in accordance with the